ANALISA PENGARUH CONTENT MARKETING TERHADAP CUSTOMER ADVOCACY DENGAN BRAND TRUST DAN CUSTOMER ENGAGEMENT SEBAGAI VARIABEL INTERVENING PADA APLIKASI TIKTOK - Ruben Theofilus Effendi (Jurnal Strategi Pemasaran, 2020)
Today's use of social media can no longer be separated from society, especially the millennial generation and generation Z. Therefore, nowadays many social media platforms are competing in order to reach a large number of users, talking about competition is not far from the word growth. Talking about growth, there is one social media platform that boomed at the beginning of the pandemic which has quite a very rapid growth, namely the TikTok platform, and what's interesting here is that the growth of TikTok users is growing in line with the growth of engagement in it which makes many companies start to look at the TikTok platform as one of the platform to channel content marketing for companies. This study aims to analyze the effect of content marketing on customer advocacy with brand trust and customer engagement as intervening variables in the TikTok application.